Does Nature use neutral beams for interstellar plasma heating around compact objects?. (7th April 2020) - Churazov, E; Khabibullin, I; Sunyaev, R
ABSTRACT: A neutral beam injection technique is employed in all major TOKAMAK facilities for heating of magnetically confined plasma. The question then arises, whether a similar mechanism might work in astrophysical objects? For instance, a hyper-Eddington Galactic binary SS433 possesses baryonic jets, moving at a quarter of the speed of light, and observations revealed signs of gas cooling and recombination on sub-pc scales and equally strong signs of powerful energy deposition on much larger scales ∼100 pc. Here, we consider a model where neutral atoms transport this energy. A sub-relativistic beam of neutral atoms penetrates the interstellar medium; these atoms gradually get ionized and deposit their energy over a region, whose longitudinal dimension is set by the 'ionization length'. The channel, where the energy is deposited, expands sideways and drives a shock in the lateral direction. Once the density in the channel drops, the heating rate by the beam drops accordingly, and the region of the energy release moves along the direction of the beam. We discuss distinct features associated with this scenario and speculate that such configuration might also boost shock acceleration of the 'pick-up' protons that arise due to ionization of neutral atoms both upstream and downstream of the shock.